Clostridium difficile beyond stools: dog nasal discharge as a possible new vector of bacterial transmission. Issue 5 (May 2019) - Rodriguez, C.; Taminiau, B.; Bouchafa, L.; Romijn, S.; Rajamäki, M.M.; Van Broeck, J.; Delmée, M.; Clercx, C.; Daube, G.
Abstract: Zoonotic transmission of Clostridium difficile has been largely hypothesised to occur after direct or indirect contact with contaminated animal faeces. Recent studies have reported the presence of the bacterium in the natural environment, including in soils and rivers. If C. difficile spores are scattered in the environment, they can easily enter the respiratory tract of dogs, and therefore, dog nasal discharge could be a direct route of transmission not previously investigated. This study reports for the first time the presence of C. difficile in the respiratory tracts of dogs. The bacterium was isolated from 6 (17.1%) out of 35 nasal samples, with a total of 4 positive dogs (19%). C. difficile was recovered from both proximal and distal nasal cavities. All isolates were toxigenic and belonged to PCR-ribotype 014, which is one of the most predominant types in animals and in community-acquired C. difficile infections in recent years. The findings of this study demonstrate that the nasal cavity of dogs is contaminated with toxigenic C. difficile, and therefore, its secretions could be considered as a new route by which bacteria are spread and transmitted.